Developing productive and creative language skills in the era of digital applications and artificial intelligence: evidence from Brunei Darussalam - Haji Ahmad, Siti Sara; Yani, Achmad; Haji Jarudin, Hajah Amalena; Sahrir, Muhammad Sabri; Bahruddin, Uril (Forester Communications Inc., 2026)
The rapid integration of digital applications and artificial intelligence (AI) has fundamentally transformed contemporary language education, particularly in relation to the development of productive and creative language skills. This study examines the pedagogical potentials, limitations, and emerging trajectories of AI-enhanced learning environments in fostering speaking and writing skills among learners of Arabic in Brunei Darussalam. Employing a descriptive–analytical library-based research design within an interpretive qualitative paradigm, the study conducts systematic content analysis of theoretical frameworks, empirical studies, and relevant policy documents on technology-enhanced language learning and artificial intelligence in education. The findings indicate that AI-supported tools—including automated writing evaluation, generative language models, speech recognition systems, and digital storytelling platforms—have become structurally transformative rather than supplementary when embedded within pedagogically guided and ethically regulated frameworks. These tools enhance linguistic accuracy, textual coherence, oral fluency, learner autonomy, and creative expression. However, the study also identifies critical pedagogical and ethical risks associated with unregulated AI use, including reduced cognitive engagement, erosion of originality, threats to academic integrity, and data-privacy concerns. Situated within Brunei’s multilingual and digitally progressive educational context, the study concludes that the sustainable future of Arabic in the digital age depends on pedagogical design, institutional vision, and ethical governance rather than technological advancement alone